Mesoporous TiO2/Zn2Ti3O8 hybrid films synthesized by polymeric micelle assembly1. Issue 78 (7th October 2015) - Zhao, Ming; Bastakoti, Bishnu Prasad; Li, Yunqi; Xu, Hua; Ye, Jinhua; Liu, Zongwen; Yamauchi, Yusuke
<x xml:space="preserve">Abstract</x> A hybrid mesoporous TiO2/Zn2Ti3O8 film synthesized by a polymeric micelle assembly approach.